A STUDY OF THE ALDOL REACTION BETWEEN ENOLATES DERIVED FROM THE IRON ACETYL COMPLEX [(ETA-5-C5H5)FE(CO)(PPH3)COCH3] AND 2,3-O-ISOPROPYLIDENE-D-GLYCERALDEHYDE - Bodwell, G; Davies, S; Mortlock, A (1991)
Diethylaluminium enolates derived from the iron acetyl complex [(η5-C5H5)Fe(CO)(PPh3)COCH3] undergo highly diastereoselective aldol reactions with the homochiral aldehyde, 2,3-O-isopropylidene-D-glyceraldehyde with the matched and mismatched pair reactions being readily identified. In both these reactions the observed diastereoselectivities may be rationalised in terms of the Masamune model for double asymmetric induction. Similarly the tin (II) enolates react in a predictable way, showing complementary diastereoselectivity, although effects attributed to enolate aggregation may suppress the mismatched pair reaction. However, the Masamune model cannot predict the results obtained with lithium enolates, where addition to the electrophile may occur under either chelation or non-chelation control. In the former case, both reagents reverse their selectivities as the initial two control elements are not mutually accommodating. © 1991.